Colonisation resistance in the sand fly gut: Leishmania protects Lutzomyia longipalpis from bacterial infection - Mauricio RV Sant’Anna; Hector Diaz-Albiter; Kelsilândia Aguiar-Martins; Waleed S Al Salem; Reginaldo R Cavalcante; Viv M Dillon; Paul A Bates; Fernando A Genta; Rod J Dillon (Parasites & Vectors, 2014)
Abstract Background Phlebotomine sand flies transmit the haemoflagellate Leishmania, the causative agent of human leishmaniasis. The Leishmania promastigotes are confined to the gut lumen and are exposed to the gut microbiota within female sand flies. Here we study the colonisation resistance of yeast and bacteria in preventing the establishment of a Leishmania population in sand flies and the ability of Leishmania to provide colonisation resistance towards the insect bacterial pathogen Serratia marcescens that is also pathogenic towards Leishmania. Methods We isolated microorganisms from wild-caught and laboratory-reared female Lutzomyia longipalpis, identified as Pseudozyma sp. Asaia sp. and Ochrobactrum intermedium. We fed the females with a sugar meal containing the microorganisms and then subsequently fed them with a bloodmeal containing Leishmania mexicana and recorded the development of the Leishmania population. Further experiments examined the effect of first colonising the sand fly gut with L. mexicana followed by feeding with, Serratia marcescens, an insect bacterial pathogen. The mortality of the flies due to S. marcescens was recorded in the presence and absence of Leishmania. Results There was a reduction in the number of flies harbouring a Leishmania population that had been pre-fed with Pseudozyma sp. and Asaia sp. or O. intermedium. Experiments in which L. mexicana colonised the sand fly gut prior to being fed an insect bacterial pathogen, Serratia marcescens, showed that the survival of flies with a Leishmania infection was significantly higher compared to flies without Leishmania infection. Conclusions The yeast and bacterial colonisation experiments show that the presence of sand fly gut microorganisms reduce the potential for Leishmania to establish within the sand fly vector. Sand flies infected with Leishmania were able to survive an attack by the bacterial pathogen that would have killed the insect and we concluded that Leishmania may benefit its insect host whilst increasing the potential to establish itself in the sand fly vector. We suggest that the increased ability of the sand fly to withstand a bacterial entomopathogen, due to the presence of the Leishmania, may provide an evolutionary pressure for the maintenance of the Leishmania-vector association.